Entanglement of N-doped graphene in resorcinol-formaldehyde: Effect over nanoconfined LiBH4 for hydrogen storage. (June 2019) - Gasnier, Aurélien; Luguet, Margaux; Pereira, Amaru González; Troiani, Horacio; Zampieri, Guillermo; Gennari, Fabiana C.
Abstract: N-doped graphene hydrogels were prepared by crosslinking graphene oxide with ethylenediamine. These materials presented 10 at. % nitrogen, as determined by X-ray photoelectron spectroscopy. N-doped graphene was entangled within mesoporous matrices by diffusion of resorcinol-formaldehyde solutions throughout the hydrogels. According to nitrogen desorption isotherms, N-doping graphene slightly reduces the pore size and volume toward values closer to the graphene-free resins. The underlying graphene framework was observed within the amorphous porous carbon by transmission microscopy. These porous materials were impregnated with LiBH4 at 30, 50 and 70 vol %. Differential scanning calorimetry of the nanoconfined hydrides illustrates how N-doped matrix promotes a decrease in LiBH4 decomposition temperature, and this effect was quantified by volumetric studies. Powder diffraction revealed a peak at 12.6° attributed to the interaction of LiBH4 with the N-doped matrix. Owing to Yates analysis, N-doping lowers hydrogen release temperature by 10 °C, while at 325 °C the quantity released is increased by 1 wt %. This effect is more important than the diminution of pore size from 10 to 5 nm and compensates the presence of graphene. The benefit from N-doping is more remarkable for lower size of pores and higher LiBH4 filling, as illustrated by the proposed model. Graphical abstract: Image 1